Особливості числового розв’язання варіаційної задачі узгодження сигналу та його нейромережева інтерпретація - Романишин, Ю.М.; Якимів, Р.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
The features of numerical solution of variation problem of matching of signal with band-pass filter – determination of minimum after energy input signal at the specified value of output signal - are considered. Procedure of determination of optimum input signal is based on the method of the dynamic programming. Neural network interpretation of the problem is considered.